Parametric Design and System Development of Different Types of Rollers Globoidal Cam Deceleration Mechanism - Chen Ruyun; Gong Qingshan; Cao Zhanlong; Sun Daocheng; Tan Hao (Jixie chuandong)
In order to improve the design efficiency of different types of rollers globoidal cam deceleration mechanism and standardize the design system, a parametric design method based on NX secondary development is proposed, and the design system is developed. According to the theory of space geometry and the principle of conjugate surface, the working profile equations of five typical types of rollers, including cylindrical roller, conical roller, ball-cone roller, drum roller and ball roller, and globoidal cam are deduced. The key design parameters are extracted, and the human-machine interaction design menus and dialogs are developed by using the NX secondary development tool. Combined with NX Open C/C++ API and Visual Studio compilation environment, the parametric design system of different types of rollers globoidal cam deceleration mechanism is developed. And according to the assembly constraint relationship between the components in the mechanism, the automatic assembly function is developed. The application shows that the whole system developed can meet the user's personalized design requirements, help to realize the normalization and standardization of the design process of different types of rollers globoidal cam deceleration mechanism, achieve the rapid design and modification, and shorten the design cycle.